Bottom-up synthesis of MoS2 nanospheres for photothermal treatment of tumors. Issue 10 (24th August 2018) - Gao, Shun; Zhou, Hailiang; Cui, Sumei; Shen, Hai
Abstract : We introduce a new nanomedicine based on spherical MoS2 nanoparticles for PTT treatment of tumors, prepared using "green" bottom-up technology. Abstract : Photothermal therapy (PTT) is providing new opportunities for killing cancer cells. In this work, we introduce a new nanomedicine based on spherical MoS2 nanoparticles for PTT treatment of tumors, prepared using "green" bottom-up technology. To increase water solubility and avoid rapid clearance by the reticuloendothelial system, polyethylene glycol (PEG) was used to coat them. These MoS2 -PEG nanospheres with an appropriate size (∼100 nm) exhibit high photothermal conversion efficiency (26.7%). In vitro cellular studies revealed that the MoS2 -PEG nanospheres showed negligible cytotoxicity. Additionally, through combining the MoS2 -PEG nanosphere samples with NIR irradiation at 808 nm, excellent in vitro tumor cell killing efficacy was achieved. In the 4T1 tumor model, the MoS2 -PEG nanospheres exhibited good antitumor efficiency in vivo, displaying complete tumor inhibition over 16 days after treatment. Therefore, MoS2 -PEG nanospheres played an important role in tumor destruction, and this concept for developing spherical MoS2 -based nanomedicines can serve as a platform technology for the next generation of in vivo PTT agents.